Curse of the Night Witch - Aster, Alex (Aster, Alex. Emblem Island, 2020)
After changing the fate he has known since birth, twelve-year-old Tor Luna, accompanied by his friends Engle and Melda, must visit the notorious Night Witch to break the curse he now faces.